Dreamings from law's dark night - R. Edwards (Law Text Culture, 1998)
Upon entering the strangeness of the North American prairie, a pioneer remarked: 'I found no path, no trail but only bush and water. Wherever I looked I saw no native land - but foreign.' A strangeness has already preceded this settler. It is the profound lack of unity between a man and his environment, a lack of sympathy with the feelings prompted by the new land. This occurrence is the incessant resettlement of space within which the man finds himself. Such is a now familiar story of exile. De Chirico speaks to the enigma when he says we should live life as if in a vast museum of strangeness, to be struck by the very presence of space and happenings. In so doing, however, we become aware that this space, in its strangeness, is no longer foreign.